(untitled) (INNOVATIVE ECONOMY, 2020)
Golomsha N.Ye., Holomsha O.Ya. RESEARCH OF COMPETITIVENESS FACTORS OF UKRAINIAN CORN IN THE WORLD MARKETS Purpose. The aim of the article is to carry out factor analysis of the parameters that determine the competitiveness of Ukrainian corn in the world markets, to substantiate their impact and to formulate a set of recommendations on the use of identified trends and patterns. Methodology of research. Methodological approaches of competition theories and international trade are combined in the process of modelling the competitiveness parameters of Ukraine in the world corn market. A factor analysis technique is used to identify the parameters of Ukrainian corn’s competitiveness in the world markets. A list of the most important factors is formed, the direction and strength of their influence on the level of competitiveness of domestic corn is determined by means of correlation-regression analysis Findings. The method of factor analysis to identify the parameters of competitiveness of Ukrainian corn in the world markets is substantiated. On the basis of correlation-regression analysis based on the combination of methodological principles of competition theories and international trade, the list of the most important factors is formed, the direction and strength of their influence on the level of competitiveness of domestic corn is determined. Unlike existing models and concepts, this approach takes into account the complex influence of competitive forces, market size, and trading conditions, which allows a high degree of probability to achieve competitiveness of Ukrainian grain in the world markets. It is found that market factors, including market capacity and population of the importing country, have positive influence on the competitiveness of Ukrainian corn in the world markets, and competitive forces (influence of direct competitors) and spatial factors, including remoteness of the main markets have negative influence. Proposals on the reaction of market participants to the objective conditions of foreign trade - market parameters, activity of competitors, conditions of trade have been developed. The expediency of intensifying export efforts in the markets of large capacity with positive population growth, which import corn from distant countries, building complex business relations with these countries, and their interest in importing Ukrainian corn, forming a comprehensive logistic advantage, is substantiated. Originality. The method of factor analysis of ensuring the competitiveness of Ukrainian corn has been improved, which results in an objective list of favourable and restraining factors, as well as substantiates the main reactions of market participants to their impact. Practical value. The obtained model results and factor dependencies form a strong methodological basis for modelling and forecasting the competitiveness of Ukrainian grain in the world markets, as well as for developing scenarios of domestic market actors’ response to the events and forces that accompany grain exports. Key words: factor analysis, competitiveness, world corn market, correlation-regression modelling, export, grain, foreign trade.